Implementasi Total Quality Management melalui Penjaminan Mutu dan Pelibatan Stakeholder dalam Penyusunan Kurikulum SMK PK - Meirani, Rosida Kerin; Supriyanto, Achmad; Imron, Ali (Kelola: Jurnal Manajemen Pendidikan, 2023)
The purpose of this study was to examine in depth the process of quality assurance and stakeholder involvement in the preparation of the SMK PK curriculum at SMKN 1 Purwosari. This research is qualitative research with descriptive method and case study design. The main data sources for the research came from school principals, deputy heads of curriculum, WMM (Deputy for Quality Management), heads of expertise programs, and industry representatives, while other parties became sources of supporting data. In-depth interviews, non-participant observation, and document review were the methods to collect the data. Collecting, condensing, presenting data, and concluding research findings were processes of data analysis. Triangulation of techniques and sources were the processes of checking the validity of the data. This study found that TPMPS (School Education Quality Assurance Team) carried out quality assurance in the preparation of the SMK PK curriculum. Stages of developing the SMK PK curriculum include analyzing the needs of school stakeholders, evaluating and planning, drafting, verifying draft, validating, and publishing. The quality aspects developed are vocational content which includes technical competencies (hard skills), non-technical skills (soft skills), and entrepreneurial skills. Stakeholders involved include internal customers, primary customers, and secondary customers.